5 3 2 1 d 1 3 x 0 0 1 figure 28 ii d x y 0

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: • [1, 1] dt = 0 3 10 1 1 − t, − (1 − t)2 • [−1, 0] dt = − 0 1 2 1 0 [0, 0] • [0, −1] dt = 0 Hence, C F • dr = Γ1 F • dr + y Γ2 F • dr + 1 F • dr = − . 5 Γ3 Γ2 1 D Γ1 Γ3 x 0 0 1 Figure 28 ii. D = {(x, y ) | 0 ≤ x ≤ 1, x ≤ y ≤ 1} (Figure 28) ∂Q ∂P ∂ ∂ − = −x2 y 2 − (x) = −2xy 2 ∂x ∂y ∂x ∂y 1 C F • dr = 0 1 x −2xy 2 dy dx = − 1 5 (c) Figure 29 F (x, y ) = [x + 2y, x − 2y ] i. Γ1 : curve y = x2 from (0, 0) to (1, 1) and r (t) = [t, t2 ] with 0 ≤ t ≤ 1 Γ2 : straight line from (1, 1) to (0, 0) and r (t) = [1 − t, 1 − t] with 0 ≤ t ≤ 1 1 Γ1 F • dr = Γ2 F • dr = t + 2t2 , t − 2t2 • [1, 2t] dt = 0 5 6 1 0 [3 − 3t, t − 1] • [−1, −1] dt = −1 2 Hence, C F • dr = Γ1 F • dr + 1 F • dr = − . 6 Γ2 y 1 Γ1 Γ2 D x 0 0 1 Figure 29 ii. D = {(x, y ) | 0 ≤ x ≤ 1, x2 ≤ y ≤ x} (Figure 29) ∂ ∂ ∂Q ∂P − = (x − 2y ) − (x + 2y ) = −1 ∂x ∂y ∂x ∂y 1 C 2 F • dr = x x2 0 (−1) dy dx = − 1 6 2 (d) F (x, y ) = [x + y , 2xy ] i. Figure 30 Γ1 : curve y = x2 from (0, 0) to (2, 4) and r (t) = [t, t2 ] with 0 ≤ t ≤ 2 Γ2 : straight line from (2, 4) to (0, 4) and r (t) = [2 − 2t, 4] with 0 ≤ t ≤ 1 Γ3 : straight line from (0, 4) to (0, 0) and r (t) = [0, 4 − 4t] with 0 ≤ t ≤ 1 2 Γ1 F • dr = Γ2 F • dr = Γ3 F • dr = t2 + t4 , 2t3 • [1, 2t] dt = 0 104 3 1 4t2 − 8t + 20, 16 − 16t • [−2, 0] dt = − 0 1 0 (4 − 4t)2 , 0 • [0, −4] dt = 0 Hence, C F • dr = Γ1 F • dr + y Γ2 F • dr + Γ3 Γ2 4 D Γ1 Γ3 x 0 0 2 Figure 30 3 F • dr = 0. 104 3 ii. D = {(x, y ) | 0 ≤ x ≤ 2, x2 ≤ y ≤ 4} (Figure 30) ∂Q ∂P ∂ ∂ x2 + y 2 = 0 − = (2xy ) − ∂x ∂y ∂x ∂y 2 C F • dr = 2. (a) D = {(x, y ) | 0 ≤ x ≤ 1, x2 ≤ y ≤ √ y+e C 1 √ = x2 0 x x √ 4 (0) dy dx = 0 x2 0 x} (Figure 31) dx + 2x + cos y 2 dy √ ∂ ∂ 2x + cos y 2 − y+e x...
View Full Document

This document was uploaded on 01/23/2014.

Ask a homework question - tutors are online